Digital Data Collection of 3 kg LPG Purchasers - Transformation of 3 kg LPG Subsidy as Implementation of the Minister of Energy and Mineral Resources Decree No. IX.37.K/KMG.01/MEM.M/2023 - Gintings, Irto Petrus; Suryanti, Nyulistiowati (Jurnal Cita Hukum, 2024)
The energy needs, especially for subsidized LPG 3 kg, have increased by more than 700% compared to the initial program of kerosene-to-LPG conversion in 2007. The 3 kg of LPG distribution is now widespread across almost all of Indonesia. Currently, 95% of LPG usage is subsidised category. As a result, subsidies for 3 kg of LPG have consistently risen annually. Meanwhile, the price gap between subsidised and non-subsidised LPG has widened, leading to widespread illegal filling practices. Ironically, eligible citizens often struggle to obtain 3 kg of LPG, due to broad criteria allowing almost anyone to purchase it. This study aims to analyze government policies aimed at more targeted subsidy transformation. Utilizing a juridical-normative research method, it examines the regulations governing the distribution of 3 kg LPG and the underlying policies for subsidy transformation. The desired outcome is for the government to ensure that the subsidy for 3 kg of LPG reaches its intended targets through adequate regulations. Revision of Presidential Regulation 104/2007 is necessary to clarify the criteria for 3 kg LPG users and enable effective implementation. Ministerial Decision No. 37.K/MG.01/MEM.M/2023 mandates businesses to gather buyer data via web-based applications, allowing cross-referencing with welfare rankings from relevant ministries/agencies based on buyer names and addresses. The digitalisation effort by government-appointed entities in data collection for 3 kg LPG buyers aims to ensure that subsidies reach the eligible Indonesian citizens.